2017
DOI: 10.1016/j.chom.2017.09.007
|View full text |Cite
|
Sign up to set email alerts
|

GBPs Inhibit Motility of Shigella flexneri but Are Targeted for Degradation by the Bacterial Ubiquitin Ligase IpaH9.8

Abstract: SummaryInterferon exposure boosts cell-autonomous immunity for more efficient pathogen control. But how interferon-enhanced immunity protects the cytosol against bacteria and how professionally cytosol-dwelling bacteria avoid clearance are insufficiently understood. Here we demonstrate that the interferon-induced GTPase family of guanylate-binding proteins (GBPs) coats Shigella flexneri in a hierarchical manner reliant on GBP1. GBPs inhibit actin-dependent motility and cell-to-cell spread of bacteria but are a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
221
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(249 citation statements)
references
References 45 publications
25
221
3
Order By: Relevance
“…A transposon‐insertion library screening then identified that the bacterial secreted effector IpaH9.8, a E3 ubiquitin ligase, was responsible for causing hGBP1 degradation, as well as the degradation of hGBP2, 4, and 6, as well as mGBP2, 3, 6, 7, 9, 10, and 11 . A role for IpaH9.8 in degrading hGBPs was independently confirmed by Wandel et al., who also showed that this restores actin‐dependent bacterial motility and cell‐to‐cell spread . Finally, Li el al .…”
Section: Introductionmentioning
confidence: 87%
“…A transposon‐insertion library screening then identified that the bacterial secreted effector IpaH9.8, a E3 ubiquitin ligase, was responsible for causing hGBP1 degradation, as well as the degradation of hGBP2, 4, and 6, as well as mGBP2, 3, 6, 7, 9, 10, and 11 . A role for IpaH9.8 in degrading hGBPs was independently confirmed by Wandel et al., who also showed that this restores actin‐dependent bacterial motility and cell‐to‐cell spread . Finally, Li el al .…”
Section: Introductionmentioning
confidence: 87%
“…Poly-ubiquitinylation of NEMO leads to its degradation in a proteasome-dependent manner, thereby dampening NF-κB activation (Ashida et al, 2010). Recently, several independent studies found that IpaH9.8 is implicated in IFN-induced antimicrobial defences and counteracts cell-autonomous immunity mediated by the family of GBPs (guanylate-binding proteins; Li et al, 2017;Piro et al, 2017;Wandel et al, 2017). Upon invasion into human IFNγ-activated cells, S. flexneri is initially targeted by human GBP1 (hGBP1), which recognises cytosol-invading Gram-negative bacteria via the LPS O-antigen and then promotes the hierarchical recruitment of additional GBP paralogs.…”
Section: Unlike the Previously Described Immunomodulatory Functions Ofmentioning
confidence: 99%
“…Furthermore, it was found that IpaH9.8 synthesises a ubiquitin‐coat on S . flexneri , which in contrast to the host‐generated ubiquitin coat does not have antimicrobial effects on the cytosolic bacteria but rather supports the pathogen, possibly through antagonising GBP recruitment (Wandel et al, ). All in all, these studies point out that targeting of GBPs by IpaH9.8 is a prerequisite for S .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to their dynamin‐like function, these GTPases have more recently been appreciated to have a multitude of roles within cell‐autonomous defenses. GBPs are also known to bring various anti‐microbial effector proteins or to stunt bacterial spread by blocking bacterial association with actin . Furthermore, GBPs can enhance inflammasome formation, which produces inflammatory cytokines in response to pathogen invasion and cellular damages …”
Section: How Do the Recruited Gtpases Disrupt Viral Rcs?mentioning
confidence: 99%